2022
DOI: 10.1038/s41598-022-16711-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of the components and molecular mechanisms of Jinshui Huanxian granules using UPLC-Orbitrap Fusion MS integrated with network pharmacology

Abstract: Jinshui Huanxian granules (JSHX) is a clinical Chinese medicine formula used for treating pulmonary fibrosis (PF). However, the effective components and molecular mechanisms of JSHX are still unclear. In this study, a combination approach using ultra-high performance liquid chromatography-Orbitrap Fusion mass spectrometry (UPLC-Orbitrap Fusion MS) integrated with network pharmacology was followed to identify the components of JSHX and the underlying molecular mechanisms against PF. UPLC-Orbitrap Fusion MS was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Therefore, inflammation is of great significance in ALI, especially chronic obstructive pulmonary disease and acute exacerbation of chronic obstructive pulmonary disease. Inflammation causes the infiltration of inflammatory cells and can release the chemokines and pro-inflammatory cytokines ( Han et al, 2022 ; Yuan et al, 2022 ). The related study has demonstrated that TNF-α, IL-1β, IL-6, IL-8, and IL-18 are most closely associated with the outcome of ALI and are the current diagnosis and prognosis method ( Parsons et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammation is of great significance in ALI, especially chronic obstructive pulmonary disease and acute exacerbation of chronic obstructive pulmonary disease. Inflammation causes the infiltration of inflammatory cells and can release the chemokines and pro-inflammatory cytokines ( Han et al, 2022 ; Yuan et al, 2022 ). The related study has demonstrated that TNF-α, IL-1β, IL-6, IL-8, and IL-18 are most closely associated with the outcome of ALI and are the current diagnosis and prognosis method ( Parsons et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 266 components were identified in JHGs. A total of 37 components in JHGs were finally established based on ultra-high-performance liquid chromatography coupled with Orbitrap Fusion mass spectrometry (MS), providing a scientific basis for the quality evaluation and control of JHGs [ 10 , 13 ]. However, pharmacokinetics and the metabolic processes of these active compounds still deserve to be elucidated by more animal experiments.…”
Section: Introductionmentioning
confidence: 99%